The relationship of visual preference for traditional village landscape with view on development approaches in China - Liang, Nian Long; Maulan, Suhardi; Mohd Yusof, Mohd Johari; Abu Bakar, Shamsul (International Information and Engineering Technology Association, 2023)
In recent years, the sustainable development of traditional Chinese village landscapes has been constantly challenged. Thus, this study intends to explore the relationship between local residents' views on development approaches and their visual preferences for traditional village landscapes, in order to guide planners and decision-makers toward more sustainable development policies and strategies that are consistent with local residents' views. The survey results from 400 participants in Guilin, Guangxi regarding visual preferences show that the local residents mostly prefer the mixed village landscape that retains the traditional characteristics of the elements while also integrating the needs for modern living and material styles. For development approaches, the results also show that the local residents believe that the development of landscapes should be based on two main views: (a) environmental preservation and (b) moderate utilization. It is also found that the views on the development approach have a significant effect on the visual preferences of traditional villages. The visual preference for the mixed-style village landscape is most affected by the development view of moderate utilization, followed by the development view of environmental preservation.